Simple rules for catalyzing collective action in natural resource management contexts - Colfer, C.J.P. (Center for International Forestry Research, 2007)
This booklet is designed to help people interested in working with small groups (usually communities or groups within communities) to reach their goals. It has been written, building first on the global literature on community based management of forests and other natural resources; secondly, on a base of experience catalyzing collective action within communities in more than 30 communities in 11 countries, using the approach called “Adaptive Collaborative Management” (ACM); and thirdly, through experience trying to catalyze collective action in two communities in Sumatra. It assumes an interest in equity, justice, and respect, as well as effective action.